ANALYSIS OF OPERATIONAL FAILURES AT PT. APP USING ROOT CAUSE ANALYSIS - Abdullah Ayman Salmin (CV. Radja Publika, 2024)
PT. APP faces significant challenges in meeting customer demands due to persistent production inefficiencies, particularly in the Kiln Dry and Finishing stages. These inefficiencies result in delays, poor product quality, and workflow disruptions, leading to customer dissatisfaction and increased operational costs. Key issues include cracks, peeling paint, and dents in the final product, which are rooted in inadequate training, outdated machinery, suboptimal methods, and environmental conditions. The study aims to analyze and address these bottlenecks to improve the company's operational performance and customer satisfaction. This research adopts a structured methodology, utilizing Root Cause Analysis (RCA) with the 5 Why technique to systematically investigate the underlying factors contributing to production inefficiencies. Complementary tools like Pareto Analysis and Fishbone Diagrams are employed to prioritize critical defects and categorize their root causes into six factors: Manpower, Machine, Materials, Methods, Measurement, and Mother Nature. Based on these analyses, practical solutions are proposed, including process standardization, equipment upgrades, enhanced quality control, and environmental controls to stabilize production conditions and reduce defects. The findings reveal that addressing the primary defects—cracks, peeling paint, and dents—can significantly enhance production efficiency and product quality. Implementing targeted interventions such as structured worker training, improved material handling, and updated equipment yielded substantial improvements in operational performance. This study highlights the importance of a systematic approach to problem-solving and provides actionable strategies for sustainable improvement, laying the groundwork for future research into advanced manufacturing technologies and sustainable practices..